The Strategic HR Leader: Driving Organizational Success Through People Management - Y. Ony Djogo (Journal of Economic, Bussines and Accounting (COSTING), 2024)
This study examines the impact of Strategic HR Leadership and People Management on Organizational Success at PT. Garuda Indonesia (Persero) Tbk, with a focus on the mediating role of Employee Performance. Utilizing a quantitative research design, data was collected from 85 employees using random sampling and analyzed with SmartPLS. The results reveal that Strategic HR Leadership has a significant positive effect on both Employee Performance and Organizational Success, indicating that effective strategic HR leadership enhances organizational success by improving employee performance. Similarly, People Management positively influences Employee Performance, which in turn contributes to Organizational Success. Although the direct effect of People Management on Organizational Success was not significant, its indirect effect through Employee Performance was notable. These findings underscore the importance of strategic HR practices and effective people management in achieving organizational success. The study provides actionable insights for enhancing HR strategies to foster a high-performing workforce and improve overall organizational outcomes.